Corporate Harm Minimisation: Promises and Perils; Comment on "Understanding Marketing Responses to a Tax on Sugary Drinks: A Qualitative Interview Study in the United Kingdom, 2019" - Jennifer Lacy-Nichols (Kerman University of Medical Sciences, 2023)
Taxes on sugary drinks are often used to encourage companies to reformulate their products to reduce the sugar content. This comment discusses how product reformulation can strengthen the market and political power of the food industry, and questions whether these political risks outweigh the public health benefits. It proposes the term 'corporate harm minimisation' to describe the strategic adaptation of a public health harm reduction strategy to align with company or industry goals. It concludes by reflecting on the other ways that corporations influence health beyond the production and marketing of 'unhealthy commodities,' and why public health actors must explore other strategies to challenge powerful corporations.